2019
DOI: 10.1186/s13075-019-1825-y
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis reprograms circadian output pathways

Abstract: ObjectiveWe applied systems biology approaches to investigate circadian rhythmicity in rheumatoid arthritis (RA).MethodsWe recruited adults (age 16–80 years old) with a clinical diagnosis of RA (active disease [DAS28 > 3.2]). Sleep profiles were determined before inpatient measurements of saliva, serum, and peripheral blood mononuclear leukocytes (PBML). Transcriptome and proteome analyses were carried out by RNA-SEQ and LC-MS/MS. Serum samples were analysed by targeted lipidomics, along with serum from mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 40 publications
0
39
0
1
Order By: Relevance
“…1), wherein the circadian clock is subject to inflammation-mediated reprogramming, with eventual disruption of the clock mechanism. 46 Immune and inflammatory responses come at a high energetic cost and therefore necessitate that immune and metabolic processes are coupled to ensure energetic demands are met. We propose that the circadian clock is such a coupling mechanism, and that during inflammation the circadian processes are extensively re-organized, with attenuation of many usual transcriptional rhythms and de novo genesis of surrogate cycling pathways.…”
Section: Inflammation Remodelling the Clockmentioning
confidence: 99%
“…1), wherein the circadian clock is subject to inflammation-mediated reprogramming, with eventual disruption of the clock mechanism. 46 Immune and inflammatory responses come at a high energetic cost and therefore necessitate that immune and metabolic processes are coupled to ensure energetic demands are met. We propose that the circadian clock is such a coupling mechanism, and that during inflammation the circadian processes are extensively re-organized, with attenuation of many usual transcriptional rhythms and de novo genesis of surrogate cycling pathways.…”
Section: Inflammation Remodelling the Clockmentioning
confidence: 99%
“…Recent studies have shown that nutritional challenges including high fat and ketogenic diets can reprogram extensively and in a tissue-specific manner the mouse circadian physiology 15 , 17 – 19 . This reprogramming is also observed in case of diseases such as rheumatoid arthritis 16 . In the present work we used the MCDD experimental paradigm to study the link between circadian timing and the development of steatohepatitis in the mouse.…”
Section: Discussionmentioning
confidence: 58%
“…Consistently, epidemiological studies increasingly support the notion that a poorly synchronized or disrupted CTS is an important risk factor for the development of many chronic metabolic diseases including dyslipidemia, overweight and insulin resistance, and cancer 11 13 . Reciprocally, circadian physiology can be altered by diseases 14 16 . This is exemplified by the reprogramming of the liver and serum metabolome as well as hepatic transcriptome occurring in obese mice 17 – 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of the rhythmic hepatic transcriptome in Klf10 Δhep mice also led to de novo oscillation for a large number of genes, reminiscent of the transcriptional changes occurring in KLF15 deficient cardiomyocytes (Zhang et al, 2015, p. 15). In addition to the genetic disruption of clock-controlled KLFs, a variety of other systemic perturbations including high fat and ketogenic diet challenges, arrhythmic feeding, calorie restriction, alcohol consumption, lung cancer and rheumatoid arthritis also generate de novo circadian oscillations in the liver (Eckel-Mahan et al, 2013;Gaucher et al, 2019;Greenwell et al, 2019;Makwana et al, 2019;Masri et al, 2016;Poolman et al, 2019;Tognini et al, 2017). Unchallenged Klf10 Δhep mice appear healthy but are prone to develop hepatic steatosis when fed with high sugar while Klf10 -/mice develop greater liver injury in a non-alcoholic steatohepatitis (NASH) model (Leclère et al, 2020).…”
Section: Discussionmentioning
confidence: 99%